PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA PEMBELAJARAN IPA DI KELAS IV SD SWADAYA TALANG PINANG - Wulan Triaheviana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2019)
Abstract: This study aims to (1) describe the application of the picture and picture learning model on science subjects in grade IV of Swadaya Talang Pinang Elementary School in Musi Banyuasin Regency, (2) describe the activities of fourth grade students at Swadaya Talang Pinang Elementary School when applied to learning models picture and picture on learning Science, (3) describes the science learning outcomes of fourth grade students of Swadaya Talang Pinang Elementary School after the application of the picture and picture learning model. This study uses qualitative research with a class action research design (CAR). The results of the pre-action research obtained an average of 54.29 with 29% grade learning completeness, the first cycle obtained an average score of 64.99 with 42.86% grade learning completeness. While in the cycle, the average grade reached 74.29 with the completeness of learning class 85.71%. Based on the results of these studies it can be concluded that through the learning model picture and picture of the science learning outcomes of grade IV SD Swadaya Talang Pinang can be improved.Keywords: Learning, IPA, Picture And Picture Model